2018
DOI: 10.1101/480558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Navigation Without and With Vision - the Role of Visual Experience and Visual Regions

Abstract: Human navigation relies on a wide range of visual retinotopic cortical regions yet the precise role that these regions play in navigation remains unclear. Are these regions mainly sensory input channels or also modality-independent spatial processing centers? Accordingly, will they be recruited for navigation also without vision, such as via audition? Will visual experience, or the lack thereof, affect this recruitment? Sighted, congenitally blind and sighted-blindfolded participants actively navigated virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…We also recently showed that V6, a classically known dorsal stream region, keeps responding to navigationrelated inputs in both congenitally blind and sighted blindfolded adults. Specifically, we showed that after short training with a minimalistic auditory SSD both groups of participants activated V6 during virtual maze auditory navigation (Maidenbaum et al, 2018) (Fig. 1).…”
Section: Computation-based Sensory-independent Cortical Organizationmentioning
confidence: 86%
See 1 more Smart Citation
“…We also recently showed that V6, a classically known dorsal stream region, keeps responding to navigationrelated inputs in both congenitally blind and sighted blindfolded adults. Specifically, we showed that after short training with a minimalistic auditory SSD both groups of participants activated V6 during virtual maze auditory navigation (Maidenbaum et al, 2018) (Fig. 1).…”
Section: Computation-based Sensory-independent Cortical Organizationmentioning
confidence: 86%
“…This would predict for instance, the activation of foveally responsive regions for Braille reading or face processing (i.e., tasks requiring high-resolution shape analyses) in the deprived primary visual cortex (Amedi et al, 2017;Heimler and Amedi, 2020). Or the activation of peripherally responsive regions during navigation tasks (Maidenbaum et al, 2018), or during auditory localization tasks (i.e., tasks requiring low-resolution shape analyses) (Fig. 1).…”
Section: Does Tssi Organization Extend To Deprived Primary Sensory Comentioning
confidence: 99%
“…In line with these results, CB participants, LB and blindfolded sighted controls learned to use an SSD to navigate in real-life size mazes. We observed that retinotopic regions, including both dorsal-stream regions (e.g., V6) and primary visual cortex regions (e.g., peripheral V1), were selectively recruited for non-visual navigation after the participants mastered the use of the SSD, demonstrating rapid plasticity for non-visual navigation (Maidenbaum et al, 2018). Moreover, the ability of participants to learn to use the SSD to detect and avoid obstacles was positively correlated with the volumes of a network commonly associated with navigation (Chebat et al, 2020; Figure 6D).…”
Section: Perceptions Of Obstacles By Congenitally Blind Individualsmentioning
confidence: 86%
“…Thus, the resulting sensations are very different from vision in the sighted, and cannot genuinely replace a missing sense for all of its functions (Moraru and Boiangiu, 2016). This is also true for task specific sensory independent regions according to the task being completed (Kupers et al, 2010a;Matteau et al, 2010;Ptito et al, 2012;Striem-Amit et al, 2012a,b;Abboud et al, 2015;Maidenbaum et al, 2018). SSDs have not become widespread in their general use by the blind population (Loomis et al, 2010;Elli et al, 2014), for various practical reasons (Chebat et al, 2018a).…”
Section: Sensory Substitution Devices (Ssds)mentioning
confidence: 99%
See 1 more Smart Citation